Forensic Anthropology Cases in Uruguay an Update (1992-2023) (London Journal of Research In Science: Natural and Formal, 2024)
The article presents an update of a quantitative analysis of the forensic anthropology cases that occurred in Uruguay from 1992 to 2023. The number of forensic anthropology cases has rapidly increased in Uruguay. Over 30 years this number had rise from 14 cases in 1992 to 75 cases in 2023, reached a maximum number of cases in 2006 and 2013, ascending to 91 cases for each year. Forensic anthropology cases processed between 1992 and 2023 at the Judicial Morgue of Montevideo ascending at the present to 1752. The Laboratory of Forensic Anthropology at the Judicial Morgue of Montevideo City was created in 1992, as a response to the need to address the backlog of cases. Since 1992 all the remains were analyzed to determine sex, stature and age at the time of death and, eventually the identity of the remains. In cases where a positive identification was made, a forensic anthropology analysis was also performed. The purpose of this paper is to describe the place of forensic anthropology in the Uruguayan medico-legal system, the evolution an increase of the number of cases from 1992 to 2023 and, to show its effectiveness in identification of human remains.
Keywords: Forensic Anthropology Cases. Forensic Anthropology Laboratory Identification. Uruguay